GREEN ACCOUNTING PRACTICES IN INDONESIAN COMPANIES - Wiratna Sujarweni; Poly Endrayanto Eko Christmawan (Universitas Tidar, 2024)
This research aims to analyze green accounting practices in Indonesia. Environmentally accounting practices are assessed using the Global Reporting Initiative (GRI). The research sample consists of companies on the Indonesia Stock Exchange that produce sustainability reports from 2020 to 2022. The descriptive analysis describes insights into environmentally friendly accounting practices in Indonesia, while the ANOVA test is used to test the differences in environmentally friendly accounting practices based on industry types and years of study. The results show that environmental disclosure in Indonesia is still deficient. The companies allocate minimal expenditure on environmental issues. The different test results show that there is no significant difference in environmental costs based on industry type, there is a significant difference in environmental disclosure based on industry type, there is no significant difference in environmental costs based on year of study, and there are significant differences in environmental disclosure based on year of study.